2018
DOI: 10.3390/md16010015
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Soft Coral Lobophytum crassum as a Producer of Anti-Proliferative Cembranoids

Abstract: Our continuous search for marine bioactive secondary metabolites led to the screening of crude extracts from a variety of aquaculture soft corals. The ethyl acetate (EtOAc) extract of Lobophytum crassum showed a distinctive chemical profile that was different from the wild type. It demonstrated significant anti-proliferative activity against Molt 4 leukemia cell with an IC50 value of 1 μg/mL after 24 h. Chemical investigation focusing on the unique peaks in L. crassum profile led to the discovery of a new α-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…13-AC exhibited a cytotoxic effect on bladder and stomach cancer cell lines by inducing apoptosis through the regulation of hnRNPs F/H and PPT1 as well as the activation p38/JNK pathway and the inhibition of PI3K/Akt growth pathways [17]. Our previous studies showed that 13-AC is an interesting compound from different perspectives including its unique chemical structure with specific functionality of α-methylene-γ-lactone, the potent cytotoxic effect against several cancer cell lines, and the high yield isolated from the cultured coral, Lobophytum crassum [16]. These compelling features encouraged us to work on this unique cytotoxic marine compound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13-AC exhibited a cytotoxic effect on bladder and stomach cancer cell lines by inducing apoptosis through the regulation of hnRNPs F/H and PPT1 as well as the activation p38/JNK pathway and the inhibition of PI3K/Akt growth pathways [17]. Our previous studies showed that 13-AC is an interesting compound from different perspectives including its unique chemical structure with specific functionality of α-methylene-γ-lactone, the potent cytotoxic effect against several cancer cell lines, and the high yield isolated from the cultured coral, Lobophytum crassum [16]. These compelling features encouraged us to work on this unique cytotoxic marine compound.…”
Section: Discussionmentioning
confidence: 99%
“…13-AC was separated from the coral Lobophytum crissum. The spectroscopic data (1D and 2D NMR) of the isolated compound were compared to those reported in the literature, and the chemical structure of 13-AC was confirmed [16]. A stock solution of 13-AC was prepared by dissolving the compound in DMSO (dimethyl sulfoxide) (20 µg/mL) and a series of dilutions was prepared before use.…”
Section: The Stock Solution Of 13-acmentioning
confidence: 96%
See 1 more Smart Citation
“…Effective drug development relies on identifying more and better bioactive compounds, such as lead molecules for subsequent modeling and synthesis, with selective killing effects against breast cancer cells. Some natural marine products have been found to inhibit proliferation [ 8 , 9 ] and induce apoptosis by modulating ROS generation [ 10 , 11 , 12 ]. Marine organisms, such as soft corals, have been found to provide highly diverse and abundant bioactive compounds against several cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…The culture of alcyonacean soft corals (Cnidaria: Anthozoa: Octocorallia: Alcyonacea)- notably Sarcophyton , Sinularia , and Lobophyton - has advanced rapidly in recent decades given the needs to (1) explore the impacts of environmental change on their physiological performance and (2) develop a sustainable supply for both the marine cosmeceutical and aquarium trade industries 1 , 7 , 8 . Many cultured soft corals used in natural product research rely on natural seawater flow-through systems (FTS) 9 , 10 ; however, natural product yields may differ from those of wild populations 11 . Other studies have used recirculating aquaculture systems (RAS) in which seawater quality parameters can be readily and automatically modulated by a variety of microprocessor-based dosing systems 12 − 14 .…”
Section: Introductionmentioning
confidence: 99%